2007
DOI: 10.1149/1.2731039
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Carbon-Coated V[sub 2]O[sub 5] Nanoparticles as a Potential Cathodic Material for Li Rechargeable Batteries

Abstract: Carbon-coated V 2 O 5 nanoparticles ͑CCV 2 O 5 ͒ are good candidates as cathodic materials for rechargeable Li batteries. These nanoparticles were prepared by burning off carbon-coated V 2 O 3 nanoparticles in air ͑around 400°C͒. The V 2 O 3 nanoparticles were prepared by a simple, single-stage reaction under autogenic pressure. Variations in the conditions of the burning process determine the properties of the carbon coating ͑e.g., thickness, weight % of carbon͒. Several types of electrodes were investigated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 32 publications
4
44
1
Order By: Relevance
“…Carboncoated V 2 O 5 nanoparticles can be synthesized via burning off carbon-coated V 2 O 3 nanoparticles around 400 8C in air. [131] The thickness and weight percentage of carbon can be manipulated by varying the conditions of the burning process. The optimal carbon content is Y. Wang and G. Cao/Developments in Nanostructured Cathode Materials Higher capacities can be achieved with vanadium oxide/ carbon nanotube nanocomposites.…”
Section: Nanostructured Carbon-oxide Compositesmentioning
confidence: 99%
“…Carboncoated V 2 O 5 nanoparticles can be synthesized via burning off carbon-coated V 2 O 3 nanoparticles around 400 8C in air. [131] The thickness and weight percentage of carbon can be manipulated by varying the conditions of the burning process. The optimal carbon content is Y. Wang and G. Cao/Developments in Nanostructured Cathode Materials Higher capacities can be achieved with vanadium oxide/ carbon nanotube nanocomposites.…”
Section: Nanostructured Carbon-oxide Compositesmentioning
confidence: 99%
“…The insertion of 2Li/V 2 O 5 corresponds to a stoichiometric energy density of 730 Wh kg 21 . 19 It was reported that V 2 19 Therefore, carbon has been introduced as a composite component to enhance the electrochemical performance, [24][25][26][27][28] i.e., the carbon increases electrical conductivity and prevents the vanadium dissolution, while the nanostructure shortens the Li + diffusion length.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25] These studies showed that crystalline V2O5 has a high specific charge but has poor cycle life behaviour since its crystal structure is damaged by prolonged charge/discharge cycles. Meanwhile, amorphous and low crystallinity V2O5 allows faster lithium-ion diffusion and displays superior cyclability.…”
Section: Introductionmentioning
confidence: 99%